A randomized trial of iPad distraction to reduce children's pain and distress during intravenous cannulation in the paediatric emergency department. Issue 5 (20th August 2020) - Ali, Samina; Ma, Keon; Dow, Nadia; Vandermeer, Ben; Scott, Shannon; Beran, Tanya; Issawi, Amir; Curtis, Sarah; Jou, Hsing; Graham, Timothy A D; Sigismund, Leanne; Hartling, Lisa
Abstract: Objectives: We compared the addition of iPad distraction to standard care, versus standard care alone, to manage the pain and distress of intravenous (IV) cannulation. Methods: Eighty-five children aged 6 to 11 years requiring IV cannulation (without child life services present) were recruited for a randomized controlled trial from a paediatric emergency department. Primary outcomes were self-reported pain (Faces Pain Scale-Revised [FPS-R]) and distress (Observational Scale of Behavioral Distress-Revised [OSBD-R]), analyzed with two-sample t-tests, Mann–Whitney U-tests, and regression analysis. Results: Forty-two children received iPad distraction and 43 standard care; forty (95%) and 35 (81%) received topical anesthesia, respectively (P=0.09). There was no significant difference in procedural pain using an iPad (median [interquartile range]: 2.0 [0.0, 6.0]) in addition to standard care (2.0 [2.0, 6.0]) (P=0.35). There was no significant change from baseline behavioural distress using an iPad (mean ± SD: 0.53 ± 1.19) in addition to standard care (0.43 ± 1.56) (P=0.44). Less total behavioural distress was associated with having prior emergency department visits (odds ratio [95% confidence interval]: −1.90 [−3.37, −0.43]) or being discharged home (−1.78 [−3.04, −0.52]); prior hospitalization was associated with greater distress (1.29 [0.09, 2.49]). Significantly more parents wished to have the same approach in the future in the iPad arm (41 of 41, 100%) compared to standard care (36 of 42, 86%) (P=0.03). Conclusions: iPad distraction during IV cannulation in school-aged children was not associated with less pain or distress than standard care alone. The effects of iPad distraction may have been blunted by topical anesthetic cream usage. Clinical trials registration: ClinicalTrials.gov: NCT02326623.